The Need for the Scaffolding Method in Students’ Mathematical Computational Thinking Process Through APOS Theory - Ardon Jamdin; Zaenuri; Scolastika Mariani; Bambang Eko Susilo (Indonesian Educational Research Journal, 2026)
The development of students’ computational thinking skills in mathematics remains a significant challenge, particularly due to the lack of adaptive instructional support that aligns with students’ cognitive stages. This study aims to analyze students’ needs for the scaffolding method in the process of mathematical computational thinking based on APOS theory. The research was conducted at Muhammadiyah Middle School Ambon using a descriptive approach with quantitative data support. The instruments used consisted of a computational thinking ability questionnaire and a scaffolding needs questionnaire. The results indicate that most students are still at the basic to intermediate levels of computational thinking and show a high need for scaffolding, especially in the action and process stages of the APOS framework. Furthermore, the findings reveal a strong relationship between students’ computational thinking ability and their need for scaffolding. These results suggest that scaffolding-based learning should be designed adaptively and systematically to support the gradual development of students’ computational thinking skills. Future research is recommended to develop and experimentally test scaffolding-based learning models that are aligned with APOS theory to enhance students’ higher-order thinking skills.